THE INFLUENCE OF MINING PROCESSING ENTERPRISE POLLUTANTS TO THE DEVELOPMENT OF OXIDATIVE STRESS AND THE ACCUMULATION OF HEAVY METALS INTO FLOWERING AND DECORATIVE PLANTS LEAVES (Ecological Bulletin of Kryvyi Rih District, 2023)
The paper presents the results of heavy metals accumulation analysis and the development of oxidative stress processes in the two species of the genus Hemerocallis leaves, which grew near a mining processing enterprise. In the industrial pollution conditions, the species-specific nature of the heavy metals accumulation by the assimilation organs of ornamental plants has beenestablished. It has been proven that H. middendorffii concentrated most of the toxic elements in its leaves during the growing season. At the same time,the high concentration of pollutants practically did not affect the general appearance of this species plants. The different intensity of heavy metal ions accumulation by the leaves of daylilies caused a certain degree of growth of free radical reactions-responses to stressors. For both studied species, a uniform and statistically significant increase in lipid peroxidation processes was establishedfrom the bud formation phase to the fruit ripening phase, as indicated by the content of TBC-active compounds in plant leaves. Thus, in H. middendorffii, despite the active absorption of most toxic elements, the development of oxidative stress was at a certain stationary level, and the amount of TBC-active compounds during the entire period of research exceeded the control indicators by only 1.2–1.4 times. In contrast, H. lilioasphodelus was more sensitive to the stressful effect of industrial pollutants.Even an insignificant level of zinc, nickel, lead, copper and cadmium against the background of a high iron content in the leaves of the species helped to increasethe intensity of formation of free radical processes twice. We can recommend using of H. middendorffii, which has a high resistance to the negative effects of industrial pollutants containing heavy metals, as a promising species both for greening the industrial territories of the mining processing enterprises and in phytoremediation techniques in urban territories.
Keywords: heavy metals; Hemerocallis L.; lipid peroxide oxidation,; TBK-active compounds